FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MELAKUKAN PEMBAYARAN PPH 21 (Orang Pribadi pada Multi Level Marketing di Surabaya) - Yulia Setyarini; Susan Susan (J-MACC, 2020)
Taxes are the main source of state revenue, one of which comes from an individual taxpayer. Taxes have a very important role to sustain development implementation and government spending. This study aims to determine the partial influence of the level of understanding of taxpayers, awareness, and tax sanctions on compliance with income taxpayer article 21 (individual taxpayer at multi level marketing in Surabaya). The research uses primary data by distributing questionnaires to individual taxpayers doing MLM work in Surabaya. The results of this study indicate that the understanding of the regulation does not partially affect taxpayer compliance because it has a significant level> 0.05 this is because the tax regulations are constantly updated resulting in a lack of understanding of taxpayers. For awareness, as well as sanctions taxation partially affect taxpayer compliance because it has a significant level <0.05.